IMPROVING STUDENTS’ SCIENTIFIC LITERACY ON ENVIRONMENTAL POLLUTION THROUGH LABORATORY-BASED LEARNING - Rubini, Bibin; Pursitasari, Indarini Dwi; Ardianto, Didit; Nugraha, Haris (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
The purpose of science education is to develop scientific literacy. This study investigated the effectiveness of Laboratory-Based Learning (LBL) in improving students’ scientific literacy. Samples were 70 seventh grade students in Bogor-West Java in which they were divided into two experimental groups, LBL and Non Laboratory-Based Learning (NLBL) group. Research instrument was scientific literacy test with 30 multiple choice questions about environmental pollution. Results suggested that both types of learning increase students’ scientific literacy, although LBL proved to create better scientific literacy improvement. Content and science process domain improvement for every indicator is discussed.